Penerapan Model Service Learning Untuk Meningkatkan Sikap Kepedulian Sosial Siswa Pada Pembelajaran IPS SD: Penerapan Model Service Learning Untuk Meningkatkan Sikap Kepedulian Sosial Siswa Pada Pembelajaran IPS SD - Karlela, Desi; Anisah, Ani Siti (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2016)
This study aims to know the students’ social awareness by service learning model. The method that is used is quantitative method with quasi-experimental design. The population in this study is all of the students in SDN Tarogong II Garut. The sample of this study is the fourth grade students which class A as experimental class and class B as control class. Service learning model is one of contextual learning that present learning based on the reality of students’ daily life.This learning model has a value if it is related with IPS subject value based in increasing the understanding of students’ social awareness because it is associated with social value. In this context,the teacher must be able to have the skill in developing many kinds of learning method that give students the base thinking in developing the students’ understanding about social attitude, in this case their social awareness. Th results of study show that results of Spearman correlation test for t-count is 11.60287 and t- table is 2. 019541. The results show that the value of t-count is bigger than t-table, so the correlation of coefficient is significant. It confirms that H0 is rejected and H1 is accepted. As conclusion, there is the influence of X variable to Y variable. It means that service learning method give significant influence to the students’ social awareness by the determination value about 76.7% which means that the effect of this category is strong/ high.